2005
DOI: 10.1002/hipo.20074
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal neurogenesis is not enhanced by lifelong reduction of glucocorticoid levels

Abstract: Neurogenesis of dentate gyrus granule cells is generally considered to be negatively regulated by glucocorticoids. We tested the hypothesis that exposure to low plasma corticosteroid levels starting in the early postnatal period enhances granule cell proliferation rate during adulthood. Rat pups were adrenalectomized (ADX) on postnatal day 10 and were then "clamped" throughout life at low corticosterone levels via oral supplementation. Neurogenesis was determined using BrdU immunochemistry at 3 and 12 months i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 78 publications
(125 reference statements)
0
17
0
Order By: Relevance
“…After Gould and colleagues (35)(36)(37) reported an increase in adult hippocampal neurogenesis in adrenalectomized rats, adrenal hormones were believed to quite generally suppress adult neurogenesis with some reports, including those on exercise effects on adult neurogenesis, challenging that paradigm (38,39).…”
Section: Discussionmentioning
confidence: 97%
“…After Gould and colleagues (35)(36)(37) reported an increase in adult hippocampal neurogenesis in adrenalectomized rats, adrenal hormones were believed to quite generally suppress adult neurogenesis with some reports, including those on exercise effects on adult neurogenesis, challenging that paradigm (38,39).…”
Section: Discussionmentioning
confidence: 97%
“…Because we used DAB as a chromogen, BrdU‐IR cells include newborn neurons and newborn glial cells. In a study that identified the phenotypes of BrdU‐IR cells, it was shown that the proportion of glial cells among newly born cells is approximately 10% (Brunson, Baram, & Bender, 2005). The same proportion between newborn neurons and newborn glial cells was also reported in rats under a 60% dietary restriction (Yanai, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Corticotropin‐releasing hormone (CRH) is a neuromodulatory peptide released from hippocampal interneurons in response to stress. Early life seizures have been shown to enhance hippocampal CRH mRNA expression in adulthood (Brunson et al., 2001b), and excessive CRH (Chen et al., 2004) and early life stress (Brunson et al., 2005) have been shown to lead to reductions in dendritic length and arborization as well as progressive cognitive deficits.…”
Section: Effects Of Seizures and Epileptogenesis On The Developing Brainmentioning
confidence: 99%